Earthquake Characteristics of Mount Semeru Eruption, East Java Year 2009 - Cholisina Anik Perwita; Sukir Maryanto; Agus Budianto (Natural B, Journal of Health and Environmental Sciences, 2012)
Type of eruption during the year 2009 can be classified into three types. Type I is a visual explosion that manifested by the eruption of contain volcanic material. Type II is the eruption of the manifestated by fog. Type III is the eruption that occurred during lava dome growth. Spectral and hypocentre analysis has been done used four seismic stations Kepolo (KPL), Leker (LEK), Tretes (TRS) and Besuk Bang (BES). From the analysis found that the correlation between visual eruption and frequency indicates that the seismic eruptions have type I has a frequency 0.87 to 3.8 Hz frequency, seismic eruption of type II has a frequency 0.87 to 2.64 Hz frequency, while the seismic eruptions type III  has a frequency 1.06 to 2.73 Hz. Result of study shows hypocenter is located at a depth of 0.90-1.47 km below the crater, interpreted as shallow magma pockets. Described based on the seismicity of 2009. Activities eruption caused by changes of pressure in deep and shallow magma pockets. The eruption process is more controlled by increase of pressure in the shallow magma pockets